2003
DOI: 10.1093/ortho/30.4.291
|View full text |Cite
|
Sign up to set email alerts
|

Orthodontic and orthognathic management of a patient with osteogenesis imperfecta and dentinogenesis imperfecta: a case report

Abstract: This case report describes a patient's severe Class III malocclusion, managed with a combination of orthodontic and orthognathic treatment. The medical history was complicated by osteogenesis imperfecta and dentinogenesis imperfecta. In addition the patient was a Jehovah's Witness. Patients with osteogenesis imperfecta carry an increased risk of perioperative haemorrhage, and this led to bimaxillary surgery being carried out as two discrete surgical episodes for the patient described. In addition, the risk of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
37
0
10

Year Published

2005
2005
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(47 citation statements)
references
References 4 publications
0
37
0
10
Order By: Relevance
“…KINDELAN et al reported a case with severe class II malocclusion, osteogenesis imperfecta and dentinogenesis imperfecta 13 . The patient was a Jehovah's Witness and could not accept blood trans- There are also risks of metabolic defects, for example OI patients experience a greater incidence of hyperthermia with general anaesthesia, which can develop into malignant hyperthermia 25 .…”
mentioning
confidence: 99%
“…KINDELAN et al reported a case with severe class II malocclusion, osteogenesis imperfecta and dentinogenesis imperfecta 13 . The patient was a Jehovah's Witness and could not accept blood trans- There are also risks of metabolic defects, for example OI patients experience a greater incidence of hyperthermia with general anaesthesia, which can develop into malignant hyperthermia 25 .…”
mentioning
confidence: 99%
“…Osteogenesis imperfecta (OI), also known as “brittle bone”, disease is a genetically determined connective tissue disorder that results from mutations of 2 genes (COL1A1 and COL1A2) responsible for the formation of type 1 collagen [13]. …”
Section: Introductionmentioning
confidence: 99%
“…Radiographically, teeth affected by DI show cervical constriction, bulbous crowns, short roots, short pulp chambers, and obliterated canals [10]. Adult patients with OI frequently exhibit class III malocclusions, anterior or posterior cross-bite, posterior open-bite, and vertical height loss [1, 3, 11]. …”
Section: Introductionmentioning
confidence: 99%
“…Because osteogenesis imperfecta is frequently associated with dentinogenesis imperfecta, deformity, impaction and agenesis of teeth can also be observed in patients suffering from this disorder 5 . Despite these functional and aesthetic problems, dental implant rehabilitation, bone graft augmentation and orthognathic surgery are extremely rare in these patients 2,4 . In particular, the treatment of a severe atrophic maxilla in osteogenesis imperfecta is challenging.…”
mentioning
confidence: 99%